Ownership structure and the cost of equity in the European context: The mediating effect of earnings management. Issue 3 (2nd January 2020) - La Rosa, Fabio; Bernini, Francesca; Verona, Roberto
Abstract : Purpose: Based on the institutionalized agency theory, this paper aims to analyses the role of earnings management (EM) in mediating the relationship between ownership structure (OS) and the cost of equity capital (COE). Design/methodology/approach: The authors test the above relationship by investigating a sample of 249 European non-financial listed companies during 2005-2012. The authors adopt different measures for both EM and COE and identify three main types of ownership by the majority share of the ultimate owners. Path analysis is used to explore the role of direct, mediated (i.e. EM) and total effects of OS on COE. Findings: While OS directly affects COE, the results support the idea that an EM-mediating effect contributes to further explain this relationship in some ownership structures. Particularly European listed family-owned firms experience lower COE owing to the prevailing direct and negative effect of OS, despite the fact that both accrual and real EM mediate and have a positive effect on COE. In financial institutions-owned firms, only a direct and positive effect can be observed on COE while state-owned firms do not have a direct influence on the COE, although they do reduce real EM, which, in turn, decreases the COE in a mediated effect. Further analysis comparing the Anglo-Saxon context with Continental Europe shows more detailed results. Practical implications: The study marks its entry into the international debate on the evolution in the value relevance of accounting information by arguing that the COE implications of EM depend on institutional factors such as OS and the context investigated. Originality/value: The paper contributes to extant finance, accounting and corporate governance literature by providing new, robust evidence on the mediating role of EM in defining COE for different ownership types and their diverse risk-taking propensities in Continental Europe, which differs from the Anglo-Saxon context both institutionally and legally.